Role of Three-Dimensional Visualization Modalities in Medical Education - Bui, Ivy; Bhattacharya, Arunabh; Wong, Si Hui; Singh, Harinder R.; Agarwal, Arpit (Frontiers in Pediatrics, 2021)
For the past two decades, slide-based presentation has been the method of content delivery in medical education. In recent years, other teaching modalities involving three-dimensional (3D) visualization such as 3D printed anatomical models, virtual reality (VR) and augmented reality (AR) have been explored to augment the education experience. This review article will analyze the use of slide-based presentation, 3D printed anatomical models, AR, and VR technologies in medical education, including their benefits and limitations.